Being Creative Inside and Outside the Classroom - Baer, John. author. aut Link
IX, 169 p.
Keywords: This book has two primary goals - to show teachers how to teach their students to be more creative thinkers and to help them to develop their own creativity as teachers - and it shows teachers how to do these things in ways that don't conflict with skill development and knowledge acquisition. In fact, teachers will learn how to teach for creativity in ways that result in improved skills and greater content knowledge. Teaching for creativity and creative teaching together will result in much higher levels of both student engagement and student learning. The book focuses on three big, well-researched ideas related to creativity training - divergent thinking, intrinsic motivation, and the CPS model of creative problem solving - and shows how to apply these ideas in designing lessons that promote creativity as well as encourage the development of content-based skills and knowledge. The book is written in a way that makes it easy for teachers to make these ideas their own, with many examples for use in K-12 classrooms.